2001
DOI: 10.1073/pnas.051436898
|View full text |Cite
|
Sign up to set email alerts
|

Neural fate of seen and unseen faces in visuospatial neglect: A combined event-related functional MRI and event-related potential study

Abstract: To compare neural activity produced by visual events that escape or reach conscious awareness, we used event-related MRI and evoked potentials in a patient who had neglect and extinction after focal right parietal damage, but intact visual fields. This neurological disorder entails a loss of awareness for stimuli in the field contralateral to a brain lesion when stimuli are simultaneously presented on the ipsilateral side, even though early visual areas may be intact, and single contralateral stimuli may still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
123
2
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(152 citation statements)
references
References 46 publications
22
123
2
5
Order By: Relevance
“…In this respect, our results seem reminiscent of recent visual studies which used fMRI to show that activation of striate and extrastriate cortex can analogously be insufficient to generate corresponding visual awareness in extinction patients (e.g. [34,42]). In the tactile domain, our results may also accord with recent evidence on unconscious somatosensory processing from a different tactile disorder.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In this respect, our results seem reminiscent of recent visual studies which used fMRI to show that activation of striate and extrastriate cortex can analogously be insufficient to generate corresponding visual awareness in extinction patients (e.g. [34,42]). In the tactile domain, our results may also accord with recent evidence on unconscious somatosensory processing from a different tactile disorder.…”
Section: Discussionsupporting
confidence: 65%
“…Using event-related potential (ERP) and/or fMRI measures to study visual extinction, several recent studies have shown that, on the one hand, relatively early components of visual processing may be abnormal for contralesional stimuli in visual extinction (e.g. [25,26,42]); while, on the other hand, extinguished visual stimuli can evidently still undergo considerable unconscious residual processing that activates intact cortical visual areas, despite being undetected (e.g. [14,15,34,42]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation is that prefrontal and modality-specific brain areas interact in creating the synesthetic experiences. This can be through associative learning (Passingham et al, 2000) and memory retrieval (Fletcher et al, 1998), or in terms of supporting the (change in) conscious perception (Kleinschmidt et al, 1998;Lumer et al, 1998;Rees, 2001;Vuilleumier et al, 2001). An alternative explanation is that the prefrontal brain areas are not involved in creating the synesthetic experiences per se, but reflect increased dependence on control mechanisms (Ridderinkhof et al, 2004).…”
Section: Projector Grapheme-color Synesthesiamentioning
confidence: 99%
“…Thus, awareness depends not only on activation in category-selective regions, but also on input from superordinate structures. Candidate regions for performing this "topdown" function include lateral prefrontal and inferior parietal cortices (Beck et al, 2001;Vuilleumier et al, 2001a). Indeed, a recent lesion study suggests a causal role for prefrontal cortex in allowing stimuli access to consciousness (Del Cul et al, 2009).…”
Section: Introductionmentioning
confidence: 99%